2021
DOI: 10.1038/s41467-021-24627-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating trophoblast cell clusters for early detection of placenta accreta spectrum disorders

Abstract: Placenta accreta spectrum (PAS) is a high-risk obstetrical condition associated with significant morbidity and mortality. Current clinical screening modalities for PAS are not always conclusive. Here, we report a nanostructure-embedded microchip that efficiently enriches both single and clustered circulating trophoblasts (cTBs) from maternal blood for detecting PAS. We discover a uniquely high prevalence of cTB-clusters in PAS and subsequently optimize the device to preserve the intactness of these clusters. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…13 Overall, the reporting of placenta percreta in the literature is based on the gross findings of hysterectomy specimens presenting with villous tissue having penetrated through the entire uterine wall, 5e12 and textbook descriptions are illustrated by diagrams showing placental villi protruding into the peritoneal cavity after crossing the myometrium and uterine serosa. 7 These diagrams have been used until today by many authors of diagnostic 14,15 and management 16 studies to describe the different grades of PAS. Luke et al 5 reported that most hysterectomy specimens arrive at the laboratory distorted by attempts to remove the placenta during delivery, limiting considerably the macroscopic examination and sampling and adding to the confusion in reporting different grades of PAS in both epidemiologic and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…13 Overall, the reporting of placenta percreta in the literature is based on the gross findings of hysterectomy specimens presenting with villous tissue having penetrated through the entire uterine wall, 5e12 and textbook descriptions are illustrated by diagrams showing placental villi protruding into the peritoneal cavity after crossing the myometrium and uterine serosa. 7 These diagrams have been used until today by many authors of diagnostic 14,15 and management 16 studies to describe the different grades of PAS. Luke et al 5 reported that most hysterectomy specimens arrive at the laboratory distorted by attempts to remove the placenta during delivery, limiting considerably the macroscopic examination and sampling and adding to the confusion in reporting different grades of PAS in both epidemiologic and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest as limited studies have examined the relationship between the numbers of circulating TBs and pregnancy complications. 30 We also found a difference between the number of patients with hypertensive disorders between the low and high FCC groups, with a similar 1.6-fold higher adjusted odds of developing hypertensive disorders of pregnancy in the high FCC group, although it was nonsignificant at p = 0.07. Nevertheless, the data suggest that the statistically significant adjusted odds for composite morbidity is in large part driven by hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 50%
“…After analyzing the data on 369 collected samples, and adjusting for the appropriate confounding variables, our results showed that composite morbidity was more prevalent in the high FCC group than in the low FCC group and that there was a 1.6‐fold odds of developing any one of these adverse pregnancy outcomes in the high FCC group. This is of particular interest as limited studies have examined the relationship between the numbers of circulating TBs and pregnancy complications 30 …”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter observational cohort study of 168 pregnant women, the combined cTB assays achieved an area under ROC curves of 0.942 (throughout gestation) and 0.924 (early gestation) for distinguishing PAS from non-PAS. For its simple operation procedure and high accuracy, the combination of cTBs and cTB clusters captured on the NanoVelcro chips for detecting PAS early in gestation will enable a promising quantitative assay to serve as a non-invasive test ( 34 ).…”
Section: Biomarkersmentioning
confidence: 99%